Charge parity violation in the minimal supersymmetric standard model (MSSM) and some new interactions - Bang, Ha Huy; Huong, Nguyen Thi Thu; Cuong, Nguyen Chinh (VNU Journal of Science: Mathematics - Physics, 2009)
Abstract